83.4k views
4 votes
Please help me with this one.​

Please help me with this one.​-example-1

1 Answer

4 votes

Answer:

2x^2 -x +1 = 0

Explanation:

For roots α and β, the original equation can be factored as ...

f(x) = 2(x -α)(x -β)

If we add 1 to each of those roots, the factors become ...

g(x) = 2(x -(α+1))(x -(β+1))

This can be rearranged to be ...

g(x) = 2((x -1) -α)((x -1) -β)

That is, we can get the desired equation by replacing x with x-1, effectively shifting the function right one unit.

2(x -1)² +3(x -1) +2 = 0

2x^2 -x +1 = 0

Please help me with this one.​-example-1
User Kliew
by
4.4k points